Characteristics and evolution of pyrobitumen-hosted pores of the overmature Lower Cambrian Shuijingtuo Shale in the south of Huangling anticline, Yichang area, China: Evidence from FE-SEM petrography. (June 2020) - Wei, Sile; He, Sheng; Pan, Zhejun; Zhai, Gangyi; Dong, Tian; Guo, Xiaowen; Yang, Rui; Han, Yuanjia; Yang, Wei
Abstract: Organic pores, one of the significant pore types in shale reservoir, can be formed in both primary organic matter (kerogen) and secondary organic matter such as solid bitumen and pyrobitumen. Compared to the primary organic pores that are mainly observed in immature kerogen, secondary organic pores in migrated organic matter (solid bitumen and pyrobitumen) are more abundant and well connected to the matrix. In this study, the petrographic characteristics between the organic matter and matrix as observed in field emission-scanning electron microscopy (FE-SEM) images were used to characterize the pore system in the overmature Lower Cambrian Shuijingtuo (Niutitang-equivalent) Shale in the south of Huangling anticline, Yichang area, China. Pyrobitumen-hosted pores were observed to be the predominant pore type in the organic-rich Shuijingtuo Shales. The porous pyrobitumen occurs primarily in the original interparticle pores filled with microcrystalline quartz, which is the primary petrographic evidence to identify the migrated organic matter. Pore-filling organic matter and precipitation of authigenic quartz, rather than mechanical compaction, resulted in further loss of a large number of interparticle pores. The porous organic matter that filled in the intraparticle space within the early-formed framboidal pyrite and the pre-existing dissolution pores within the quartz and pyrite grains is pyrobitumen. This pyrobitumen had migrated as a mobile phase into the aforementioned pores spaces in the initial phase of hydrocarbon emplacement during the petroleum expulsion and migration process. With increasing thermal maturity, this migrated organic matter thermally transformed into pyrobitumen, and nanoscale pores were developed with thermal cracking into gas. The results show that the pore volume and surface area are positively correlated with the total organic carbon (TOC) content, indicating that organic matter primarily controls shale porosity for the Shuijingtuo Shales. Highlights: Pyrobitumen-hosted pores are the predominant pore type in the organic-rich Shuijingtuo Shale. The porous pyrobitumen primarily occurred in the original intergranular pores. The lack of interparticle pores is mainly caused by the late cementation and filling by organic matter. The organic matter is the prominent factor controlling the shale porosity for the Shuijingtuo Shale studied in this work.